Vector-like exotics in F-theory and 750 GeV diphotons - Palti, Eran (Nuclear physics. B, Particle physics, 2016)
The recent excess in diphoton events around 750 GeV seen by the ATLAS and CMS experiments could be hinting at the existence of new vector-like charged matter around the TeV scale which couples to a singlet. Such a spectrum of exotics arises inevitably in certain classes of F-theory GUTs with hypercharge flux when the GUT symmetry is extended by a U(1) symmetry under which the Higgs fields of the MSSM are not vector-like. The exotics are not vector-like under the U(1) symmetry and therefore their mass is naturally related to its breaking scale. Previously this scale was taken to be close to the GUT scale which led to tension with proton decay, the μ-term magnitude, and too large R-parity violation. The 750 GeV excess provides new motivation for considering breaking the U(1) around the TeV scale, which additionally alleviates the previous problems. We study the possible TeV-scale spectrum in such an SU(5) GUT scenario and show that it is constrained and predictive. Gauge coupling unification can be retained at the accuracy of the MSSM at one loop even though typically the spectrum does not form complete GUT representations. For example the exotics cannot form a complete 10 multiplet but nonetheless happen to behave as one in the beta functions. We present an initial analysis of the diphoton production rates for the exotics spectra and find them compatible with data.